New species and new synonyms of Macromotettixoides (Orthoptera: Tetrigidae) with an updated key - Deng, Wei-An; Xin, Lei; Zhang, Rong-Jiao; Huang, Chao-Mei; Xu, Hai-Qing; Tan, Liu-Su; Huang, Su-Qin (Zootaxa, 2020)
The genus Macromotettixoides Zheng, Wei & Jiang, 2005 is reviewed. Four new species of the genus, M. daiyunshanensis Deng, sp. nov., M. curvicarina Deng, sp. nov., M. convexa Deng, sp. nov. and M. shengtangshanensis Deng, sp. nov. are described with detailed illustrations of external morphology. Two new synonyms are established: M. jinggangshanensis, syn. nov. is synonymized with M. jiuwanshanensis Zheng, Wei & Jiang, 2005; M. parvula Zha & Wen, 2017, syn. nov. is synonymized with M. undulatifemura Deng, Zheng & Yang, 2012. Additionally, an updated key to species of the genus is given.